Study on the Compression Moulding of Intercrossed Pre-Preg Glass FiberReinforced Plastic - Kim, J.W. (Проблемы прочности, 2016)
In this paper, pre-preg intercrossed GFRP composite is cut in the square and undergone through hot compression moulding. During this process, flow front of actual sample and simulation results with finite element method (FEM) is compared. Pre-preg intercrossed GFRP composite is made of stacking plain weaved pre-preg, and material cannot be slipped by the entanglement between fibers. Based on the assumption of the significant influence of friction, α = 100 of slip parameter is used in FEM flow analysis according to the Galerkin method, which is well matched to experimental results.